Pengaruh Budaya Organisasi, Lingkungan Kerja Fisik, dan Lingkungan Kerja Non Fisik terhadap Kinerja Karyawan pada UD. Sumber Rejeki - Muhammad Aldy Alamsyah; Miftahul Munir; Anita Sumelvia Dewi (Kajian Ekonomi dan Akuntansi Terapan, 2025)
This study assesses the influence of organizational culture, physical work environment, and non-physical work environment on employee performance at UD. Sumber Rejeki. Organizational culture is understood as the values, norms, and patterns of behavior agreed upon by members. The physical work environment refers to tangible conditions such as layout, lighting, and cleanliness. The non-physical work environment relates to the psychological climate and social relationships in the workplace. The research design is quantitative with a census or saturated sample technique. All 32 employees were respondents. The instrument was compiled using a Likert scale. The data were processed using SPSS 25. The analysis stages included validity, reliability, normality, multicollinearity, heteroscedasticity, multiple linear regression, t-test for partial effects, f-test for simultaneous effects, and the coefficient of determination R². The partial test results showed that organizational culture did not have a significant effect on employee performance. Conversely, the physical work environment and non-physical work environment had a positive and significant effect. The simultaneous test confirmed that the three variables together had a positive and significant effect on performance. These findings indicate that improvements in physical aspects such as room comfort, equipment, and safety standards, as well as strengthening non-physical aspects such as supervisor support, role clarity, and communication, are more directly related to performance improvement than existing cultural characteristics. In practical terms, management needs to prioritize programs to improve the physical work environment and psychological climate, accompanied by periodic evaluations so that the impact can be measured against performance indicators.